2007
DOI: 10.1177/1934578x0700201111
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoidine L, A New Antibacterial Flavonoid from Erythrina Sigmoidea (Fabaceae)

Abstract: Chemical analyses of the stem bark of Erythrina sigmoidea (Fabaceae) yielded a new flavonoid, designated sigmoidin L (1), the known erythrinasinate, E-p-coumaric acid docosylester, and 3′-prenylnaringinin, reported here for the first time for the stem bark of E.sigmoidea. The structure of 1 was established by chemical and spectroscopic means as 5,7, 3′,4′-tetrahydroxy-5′-[3″-methyl-4″-oxobut-(1″Z) enyl]flavanone. Sigmoidin L exhibited significant antibacterial potency in vitro against Staphylococus aureus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Flavonoid compounds, which are a large group of secondary metabolites in higher plants [ 1 ], are known to be responsible for antioxidant [ 2 , 3 ], anticancer [ 4 , 5 ], anti-inflammatory [ 6 , 7 ], hepatoprotective potential [ 8 , 9 ] and antibacterial activity [ 10 , 11 ]. Recently, epidemiological studies have strongly suggested that consumption of plant flavonoids contributes to reducing the risk or incidence of some cancers [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid compounds, which are a large group of secondary metabolites in higher plants [ 1 ], are known to be responsible for antioxidant [ 2 , 3 ], anticancer [ 4 , 5 ], anti-inflammatory [ 6 , 7 ], hepatoprotective potential [ 8 , 9 ] and antibacterial activity [ 10 , 11 ]. Recently, epidemiological studies have strongly suggested that consumption of plant flavonoids contributes to reducing the risk or incidence of some cancers [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the molecular formula, there was a second hydroxyl group in 1, which on a biogenetic basis was assumed to be at C-3 [3]. Furthermore, the 1 H and 13 C NMR data of the aglycone (Tables 1 and 2), as well as the IR and MS evidence (see Experimental), were consistent with structure 3.…”
mentioning
confidence: 74%
“…The IR spectrum of 1 disclosed absorptions due to a δ-lactone carbonyl (1725 cm -1 ), aromatic ring (1625, 1604, 1500 cm -1 ) and aromatic C-O (1222 cm -1 ), as well as UV absorption maxima at 246, 315 and 353 nm, indicating the presence of a coumestan skeleton [1b,1f,2]. Furthermore, absorption bands at 3410-3200 cm -1 and the positive response to the FeCl 3 According to the molecular formula, there was a second hydroxyl group in 1, which on a biogenetic basis was assumed to be at C-3 [3]. Furthermore, the 1 H and 13 C NMR data of the aglycone (Tables 1 and 2), as well as the IR and MS evidence (see Experimental), were consistent with structure 3.…”
mentioning
confidence: 99%
“…Flavonoids have been known for a long time to exert diverse biological effects [1,2] and are widespread in the plant kingdom. The genus Erythrina (Fabaceae) has a significant history of folkloric use for the treatment of various diseases [3]. Previously we reported sigmoidin L [3], an anti-bacterial flavonoid from E. sigmoidea, a Cameroonian medicinal plant.…”
mentioning
confidence: 99%
“…The genus Erythrina (Fabaceae) has a significant history of folkloric use for the treatment of various diseases [3]. Previously we reported sigmoidin L [3], an anti-bacterial flavonoid from E. sigmoidea, a Cameroonian medicinal plant. As a continuation of our phytochemical studies of the neutral compounds of this species, we now report the isolation and structural elucidation of two flavonoids, namely 5,7-dihydroxy-3′-O-prenyl-(3′′,4′′-dihydroxy-2′′,2′′-dimethylpyrano)[5′′,6′′:4′,5′]flavanone (1) and 5,7,3′-trihydroxy-(3′′-hydroxy-2′′-(1-hydroxyisopropyl)-[4′,5:4′′,5′′]furanoflavanone (2).…”
mentioning
confidence: 99%